PEDAGOGICAL MODELS AND ORGANIZATIONAL-PEDAGOGICAL CONDITIONS FOR REPRESENTING THE IMAGE OF ANCESTORS - Xaitov Zufar Asroralievich (International Journal of Literature and Language Studies, 2026)
This article discusses the pedagogical models and organizational-pedagogical conditions for representing the image of ancestors in the educational process. Special attention is paid to the role of visual arts in educating students in the spirit of national pride, respect for historical heritage, and devotion to national values. The study emphasizes that portraying the images of great ancestors through portraiture, miniature art, composition, tonal solution, and holistic perception has significant educational and aesthetic importance. The article analyzes the methodological possibilities of using artistic images of historical figures in developing students’ creative thinking, aesthetic taste, visual perception, and patriotic feelings. It also highlights the importance of organizing practical art lessons on the basis of national heritage, historical memory, and cultural continuity. In this process, students not only acquire technical skills in drawing and composition, but also develop a deeper understanding of the moral, spiritual, and educational significance of their ancestors’ legacy.